Controlled Release Oral Delivery System Containing Water Insoluble Drug - Thapa, Panna; Ghimire, Manish; Mullen, Alex B.; Stevens, Howard N.E. (Kathmandu University Journal of Science, Engineering and Technology, 2005)
The objective of this study was to formulate a controlled release oral delivery system and to investigate the influence of different diluents, Carbopol 934P concentration, and granulation technique on the release of a poorly water-soluble drug (Ibuprofen) from Carbopol 934P matrix tablets. Matrix tablets were prepared by direct compression, wet granulation, and dry granulation methods at different polymer concentrations using lactose, dibasic calcium phosphate (DCP), microcrystalline cellulose (MCC), and starch as diluents. Dissolution studies were carried out in 900 ml phosphate buffer pH 7.4 using USP-apparatus I. At 5% Carbopol 934P concentration, the t50% was found in the rank order of tablets containing starch < MCC < DCP < lactose. The integrity of tablets and drug release were primarily governed by the properties of diluents at low polymer concentration. At 12.5% Carbopol 934P concentration, the t50% was found in the rank order of tablets containing MCC < DCP < Starch < Lactose. The effect of polymer predominated as the polymer concentration increased. Similar release profiles were observed at 20% Carbopol 934P concentration with t50% (>9hrs). Drug release rate decreased with polymer concentration. Granulation technique had an appreciable effect on the drug release profile which was in the rank order of direct compression < dry granulation < wet granulation (alcohol) < wet granulation (water). There was a significant effect of granulation technique, polymer concentration on the drug (Ibuprofen) release rate from Carbopol 934P matrix-based tablets (ANOVA, p<0.05). Diluents have an appreciable effect on the drug release rate only at low polymer concentration.